Responses of Nitrogen Utilization and Apparent Nitrogen Loss to Different Control Measures in the Wheat and Maize Rotation System - Peng, Zhengping; Liu, Yanan; Li, Yingchun; Abawi, Yahya; Wang, Yanqun; Men, Mingxin; An-Vo, Duc-Anh (Frontiers in Plant Science, 2017)
Nitrogen (N) is an essential macronutrient for plant growth and excessive application rates can decrease crop yield and increase N loss into the environment. Field experiments were carried out to understand the effects of N fertilizers on N utilization, crop yield and net income in wheat and maize rotation system of the North China Plain (NCP). Compared to farmers’ N rate (FN), the yield of wheat and maize in reduction N rate by 21-24% based on FN (RN) was improved by 451 kg ha-1, N uptakes improved by 17 kg ha-1 and net income increased by 1671 CNY ha-1, while apparent N loss was reduced by 156 kg ha-1. The controlled-release fertilizer with a 20% reduction of RN (CRF80%), a 20% reduction of RN together with dicyandiamide (RN80%+DCD) and a 20% reduction of RN added with nano-carbon (RN80%+NC) all resulted in an improvement in crop yield and decreased the apparent N losses compared to RN. Contrasted with RN80%+NC, the total crop yield in RN80%+DCD improved by 1185 kg ha-1, N uptake enhanced by 9 kg ha-1 and net income increased by 3929 CNY ha-1, while apparent N loss was similar. Therefore, a 37-39% overall decrease in N rate compared to farmers plus the nitrification inhibitor, DCD, was effective N control measure that increased crop yields, enhanced N efficiencies, and improved economic benefits, while mitigating apparent N loss. There is considerable scope for improved N use effieincy in the intensive wheat -maize rotation of the NCP.